(untitled) (Experimental biology, 2016)
Mechanisms of chronic inflammation significantly differ from mechanisms of acute inflammation, which is morphologically characterized by the presence of mast cells, neutrophils and macrophages. In the case of unresolved acute inflammation, by reasons not fully elucidated, a chronic inflammation develops, which is characterized by the presence of T-lymphocytes, macrophages and fibroblasts. Taken together, these cells support prolonged chronic inflammation, a characteristic feature of which is the phenomenon of the simultaneous presence of proinflammatory and anti-inflammatory cytokines. We hypothesized that the key role in this process belongs to so-called myeloid derived suppressor cells (MDSC), which represent a heterogeneous population of early hematopoietic progenitors of myelomonocytic branch (neutrophils and monocytes), and are identified in mice by expression of CD11b and Gr-1 markers and the ability to inhibit NK and cytotoxic T cell activity. We suggested that MDSC phenomenon is not a prerogative of cancer process but most probably is linked to pathogenesis of chronic inflammation, which precedes and to a certain extent induces carcinogenesis. The aim of the study was a flow cytometric analysis of different MDSC subpopulations (G-MDSC and M-MDSC) in mice with adjuvant arthritis, a classic experimental model of chronic inflammation. Flow cytometry was used as the main method, the applicability of which to the phenotypic evaluation of MDSC was confirmed earlier by Ehrlich carcinoma subcutaneous model in CBA mice. As it turned out, tumor growth correlated with an increase in splenic CD11b+Gr-1+ MDSCs. According to our data, development of local chronic inflammation also resulted in an elevated level of circulating MDSCs. By the end of two weeks after administration of complete Freund’s adjuvant (CFA) in the hind limb of CD-1 mice, we showed a more than two-fold increase of total MDSC in the spleen, in both monocyte (M-MDSC) and granulocyte (G-MDSC) MDSC fractions. The increase in MDSCs persisted until forth week. Also, we found a significantly increased level of CD11b+Gr-1+ cells expressing CD184 (CXCR4). In addition, by the end of the fourth week of the chronic inflammation, we observed an increase in MDSCs expressing CD195+ (CCR5+), and an increased proportion of CD62+ MDSC by the second week. Thus, the processes, associated with the development of local chronic inflammation lead to an increase in the spleen levels of MDSCs and their ability to migrate into the inflammatory sites by increasing the expression of receptors to SDF-1α and RANTES chemoattractants.